Market Access for Sale : Latin America's Lobbying for U.S. Tariff Preferences - Kee, Hiau Joo (The World Bank, 2004)
Kee, Olarreaga, and Silva assess the foreign lobbying forces behind the tariff preferences that the United States grants to Latin American and Caribbean countries. The authors extend the basic framework developed by Grossman and Helpman (1994) to explain the relationship between foreign lobbying and tariff preferences. Their results suggest that returns to Latin American and Caribbean exporters lobbying for tariff preferences in the United States are around 50 percent. The reason for these large returns is the relatively low estimated weight given to social welfare in the U.S. government's objective function when deciding whether or not to grant tariff preferences to Latin American and Caribbean exporters. This paper—a product of Trade, Development Research Group—is part of a larger effort in the group to study the issues related to trade and growth